ICER 2016, and Star Trek at 50. - Guzdial, Mark; Reed, Daniel A. (Communications of the ACM, 2016)
The article discusses several papers presented and awards distributed at the 2016 International Computing Education Research (ICER) in Melbourne, Australia, and the significance of television series "Star Trek" and "Star Trek" movies and films upon the 50th anniversary of "Star Trek" network television premiere. It discusses papers by scholars such as Elizabeth Patitsas on computer science (CS) grades, scholars Alex Lishinski, Aman Yadav, Jon Good, and others on the topic of gender differences and CS students, and a paper by scholars Craig S. Miller and Amber Settle.